2018
DOI: 10.1590/0037-8682-0215-2017
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycosis, a lurking threat: a report of 11 cases and literature review

Abstract: Actinomycosis remains characteristically uncommon, but is still an important cause of morbidity. Its clinical presentation is usually indolent and chronic as slow growing masses that can evolve into fistulae, and for that reason are frequently underdiagnosed. Actinomyces spp is often disregarded clinically and is classified as a colonizing microorganism. In this review of literature, we concomitantly present 11 cases of actinomycosis with different localizations, diagnosed at a tertiary hospital between 2009 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Perforated appendicitis is the most frequent cause of this subtype [ 8 ]. It can also be related to abdominal trauma, recent abdominal surgery, diverticulitis, abdominal perforation, neoplasia [ 3 - 6 ], or the use of intrauterine contraceptive devices [ 3 , 6 , 7 ]. There are also reported cases associated with poor dental hygiene [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perforated appendicitis is the most frequent cause of this subtype [ 8 ]. It can also be related to abdominal trauma, recent abdominal surgery, diverticulitis, abdominal perforation, neoplasia [ 3 - 6 ], or the use of intrauterine contraceptive devices [ 3 , 6 , 7 ]. There are also reported cases associated with poor dental hygiene [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It affects predominantly in the cervicofacial region, followed by abdominal and thoracic regions [ 4 - 6 ]. Perforated appendicitis is the most frequent presentation of abdominal actinomycosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can affect many sites of humans, such as the cervicofacial (50-60%), thoracic actinomycosis (15-20%), abdominopelvic (20%), the central nervous system (2%), and rarely involves cutaneous, ophthalmic, musculoskeletal disease, pericarditis, genitourinary or disseminated disease [5]. As for thoracic actinomycosis, the most common etiology of infection is poor dental hygiene and diabetes, HIV infection, malignancies, steroid, obesity, alcoholism, and age > 65 years are risk factors for developing thoracic actinomycosis [6]. Otherwise, patients with chronic obstructive pulmonary disease, pulmonary sequelae following tuberculosis and with the aspiration of foreign bodies [7,8], are considered to also be risk factors [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, risk factors associated with the acquisition of Actinomyces are immunosuppression, diabetes and between 20-year-old and 60-year-old age group 15. In a paper by Paulo et al , 10 out of the 11 patients reported to have at least one factor of immunosuppression 18. Given the rarity of such infection in general across the population, the authors have called for patients to be screened for HIV infection and malignancies.…”
Section: Discussionmentioning
confidence: 99%